Commemorating the Indian National Army in Singapore, 1945-2011 - RETTIG, Tobias Frederik (Institutional Knowledge at Singapore Management University, 2011)
This paper sketches how the Indian National Army has been publicly commemorated (or not) in Singapore from 1945 to the present. It will do so by looking at symbolically important acts such as the creation of the INA memorial by Subhas CHANdra Bose dedicated to the unknown Indian soldiers and its blowing up by the British (both in 1945), a series of oral history interviews undertaken in the 1980s by the National Archives, and the erection of a memorial plaque in 1995, and more recent initiatives and events (e.g. book launchs relating to the INA).The paper also intends to situate the commemoration of the INA and its key leaders, such as Subhas CHANdra Bose or Captain Lakshmi Sahgal (and others who would rise to prominence in post-colonial Malaya), in the wider context of Singapore’s commemoration of World War II. Where does the INA fit in comparison with World War II heroes such as Lim Bo Seng, Lieutenant Adnan, or Elizabeth Choy, villains such as Lai Teck, and other individuals or organizations that occupy more ambivalent positions?